Gender Bias in Residents’ Perceptions and Support of Rally Event Tourism: The Sierra Morena Rally of Córdoba, Spain - José E. Ramos-Ruiz; Miguel Ángel Solano-Sánchez; Lucía Castaño-Prieto; Minerva Aguilar-Rivero (Administrative Sciences)
Motorsports have become a tourism resource for certain territories. Knowledge about the perception of impact and the support residents provide for their celebration contributes to ensuring their long-term success. The academic literature has so far focused on large-scale events, leaving a gap in knowledge regarding small-scale events. This study addresses the case of the Sierra Morena Rally in Córdoba, Spain. It is based on the principles of Social Exchange Theory (SET) and Social Representation Theory (SRT) to explore a gender bias in the perception of impact and support for the event. Using a sample of 753 residents, an Exploratory Factor Analysis is conducted, and Mann–Whitney U and Hedges’ G statistics are applied. The results confirm the existence of a gender bias in perception, which is discussed in the context of previous case studies.